Incidence of BK polyomavirus infection after kidney transplantation is independent of type of immunosuppressive therapy. Issue 6 (30th November 2016) - Radtke, Josephine; Dietze, Nina; Fischer, Lutz; Achilles, Eike‐Gert; Li, Jun; Scheidat, Silke; Thaiss, Friedrich; Nashan, Bjoern; Koch, Martina
Abstract: Background: BK polyomavirus (BKV) infection and BKV nephropathy (BKVN) are risk factors for allograft function and survival. Methods: We retrospectively analyzed BK viremia and BKVN in 348 patients who received a kidney transplantation donated after brain death (n=232) or living donation (n=116) between 2008 and 2013. A total of 266 patients were treated with standard immunosuppression consisting of basiliximab induction, calcineurin inhibitor (CNI), and mycophenolic acid (MPA, n=219) or everolimus (n=47); 82 patients received more intense immunosuppression with lymphocyte depletion, CNI and MPA (n=38) or everolimus (n=44). Results: BK viremia occurred in 33 (9.5%) patients in the first year and in 7 (2.0%) recipients in the second year after transplantation. BKVN occurred in 4 (1.1%) patients in the first year. Donor and recipient age, diabetes, previous transplantation, and type of transplantation (donated after brain death vs living donation) were not risk factors ( P >.05). BK incidence did not differ depending on induction or maintenance immunosuppression. Conclusion: Incidence of BK viremia is independent of recipient characteristics, type of transplantation as well as induction and maintenance immunosuppression.